2022
DOI: 10.1038/s41467-022-31418-w
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine deficiency in solid tumor cells confers resistance to ribosomal RNA synthesis inhibitors

Abstract: Ribosome biogenesis is an energetically expensive program that is dictated by nutrient availability. Here we report that nutrient deprivation severely impairs precursor ribosomal RNA (pre-rRNA) processing and leads to the accumulation of unprocessed rRNAs. Upon nutrient restoration, pre-rRNAs stored under starvation are processed into mature rRNAs that are utilized for ribosome biogenesis. Failure to accumulate pre-rRNAs under nutrient stress leads to perturbed ribosome assembly upon nutrient restoration and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Recently, it has been shown that under nutrient‐deprived conditions, the source of acetyl‐CoA is changed from citrate to acetate in cancer cells by the enzyme ACSS2, which produces acetyl‐CoA from acetate 34–37 (Figure 2). We also reported that glutamine deprivation makes cancer cells resistant to the RNA polymerase I inhibitor through an impaired p53 activation pathway 13 . Furthermore, it has been shown that SREBP2 , a regulator of cholesterol metabolism, is activated in acidic pH environments, which also induces metabolic shifts 14 .…”
Section: Metabolic Adaptations Of Cancer Cells In Tmesmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, it has been shown that under nutrient‐deprived conditions, the source of acetyl‐CoA is changed from citrate to acetate in cancer cells by the enzyme ACSS2, which produces acetyl‐CoA from acetate 34–37 (Figure 2). We also reported that glutamine deprivation makes cancer cells resistant to the RNA polymerase I inhibitor through an impaired p53 activation pathway 13 . Furthermore, it has been shown that SREBP2 , a regulator of cholesterol metabolism, is activated in acidic pH environments, which also induces metabolic shifts 14 .…”
Section: Metabolic Adaptations Of Cancer Cells In Tmesmentioning
confidence: 88%
“…We have previously investigated multilayered analyses in hypoxia and nutrient starvation and reported that hypoxia, nutrient starvation, and acidic pH had distinct genetic, epigenetic, and metabolic regulations. 8,13,14 Other tumor microenvironmental stress is known as ER stress.…”
Section: Me Tabolic Adap Tations Of C An Cer Cell S In Tme Smentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that GCN2 also supports RiBi reprogramming. The adaptive cellular response to starvation implicates limitation of both RNA Pol I activity and rRNA processing (Pan et al, 2022). Our data supports a model in which GCN2 preserves the repression of 47S expression in amino acid-depleted conditions likely to sustain the translational dedifferentiation program.…”
Section: Discussionmentioning
confidence: 99%